2003
DOI: 10.1002/app.13367
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical polymerization of fluoro‐ and chloro‐substituted anilines and copolymers with aniline

Abstract: Poly(2-fluroaniline) and poly(2-chloroaniline) were synthesized by an electrochemical method in an acetonitrile solution containing tetrabutylammonium perchlorate and perchloric acid. Also, the electrochemical copolymerization of aniline with 2-fluroaniline and 2-chloroaniline was carried out in the same medium. Cyclic voltammograms of the deposited films were recorded in neutral, acidic, and basic solutions. The electrochemical behavior of the films showed the same characteristic results as conventional polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Pekmez-Ö zcicek et al [11] reported that incorporation of aniline units within polythiophene chains led to copolymers having an increased range of electrochemical stability. on the conductivities of poly(aniline-co-2-flouroaniline) and poly(aniline-co-2-chloroaniline) [12]. Monomers bearing sulfonate, alkylsulfonate and carboxylate groups were copolymerized with aniline, yielding self-doped copolymers [13].…”
Section: Introductionmentioning
confidence: 99%
“…Pekmez-Ö zcicek et al [11] reported that incorporation of aniline units within polythiophene chains led to copolymers having an increased range of electrochemical stability. on the conductivities of poly(aniline-co-2-flouroaniline) and poly(aniline-co-2-chloroaniline) [12]. Monomers bearing sulfonate, alkylsulfonate and carboxylate groups were copolymerized with aniline, yielding self-doped copolymers [13].…”
Section: Introductionmentioning
confidence: 99%
“…The primary advantage of copolymerization is that the properties of the resulting material (copolymer) can be regulated by adjusting the ratio of the monomer concentrations [30]. Several reports are available on aniline or substituted aniline-based copolymers [31][32][33][34][35][36][37]. In many cases the copolymers exhibit better properties than the homopolymers [38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed FTIR interpretation is presented elsewhere [39]. The XRD pattern of POC hollow microspheres shows that the product is amorphous and only one broad peak centered at 2θ =25 o may be ascribed to the periodicity parallel to the polymer chain [42,43]. The XRD pattern of the POC hollow microsphere was presented in our previous studies [39].…”
Section: Structural Characterizationmentioning
confidence: 99%